Bergey's Manual of Systematics of Archaea and Bacteria 2016
DOI: 10.1002/9781118960608.gbm01180.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Methylocaldum

Abstract: Me.thy.lo.cal'dum. N.L. pref. methylo ‐ pertaining to the methyl radical; L. adj. caldus hot; N.L. neut. n. Methylocaldum heat‐loving methylotroph. Proteobacteria / Gammaproteobacteria / Methylococcales / Methylococcaceae / Methylocaldum Gram‐negative, coccoidal to long rods . Moderately thermophilic ; growth at temperatures >40°C. Ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…A signature characteristic of Methylocaldum strains is the development of light to dark brown-colored colonies/culture [ 63 ]. Previous analyses showed that M. szegediense O-12 synthesizes a tyrosine-derived melanin-like pigment upon a decrease in growth temperature (at a suboptimal temperature of 42 °C) [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…A signature characteristic of Methylocaldum strains is the development of light to dark brown-colored colonies/culture [ 63 ]. Previous analyses showed that M. szegediense O-12 synthesizes a tyrosine-derived melanin-like pigment upon a decrease in growth temperature (at a suboptimal temperature of 42 °C) [ 64 ].…”
Section: Resultsmentioning
confidence: 99%